Digital transformation of oil and gas companies to improve their performance (Economics and region, 2024)
The digital transformation of the oil and gas industry, as well as other sectors of the economy, is a prerequisite for successful operation in an uncertain and rapidly changing market. The use of digital technologies by oil and gas companies will improve the communication between different entities (oil and gas production and service companies), develop the working structure of each entity and ensure their long-term sustainability in an unstable market environment. The study substantiates the benefits of digital transformation of oil and gas enterprises to improve their performance. The necessity of developing a digital strategy for the oil and gas industry entities is proved. The author notes that the coordinated implementation of digital solutions prevents margin migration between different market participants and stimulates a more active exchange of innovations that will contribute to the long-term development of the industry. Partnership strategies in digital transformation not only increase the resilience of companies to external risks, but also form the basis for future growth through technological improvement. An ontological model of the positive effects of digitalization of exploration, development and production processes in the oil and gas industry is presented. It is substantiated that the use of machine learning for field exploration significantly improves the ability of geologists to visualize and analyze geological data. The use of artificial intelligence algorithms allows to reveal geographical structures and patterns that are difficult to detect using traditional methods. It is proved that the introduction of sensing in the process of mineral extraction provides a higher level of control over all stages of extraction and processing of resources, which contributes to the efficiency and safety of production processes. Overall, the study results suggest that digital solutions are not only a means to increase the productivity of the oil and gas industry, but also a tool to ensure its long-term sustainability, adaptation to new challenges, and competitive advantage in the global market.
Keywords: digital transformation; upstream and service companies of the oil and gas industry; machine learning; artificial intelligence